Light-induced charge transfer in pyrene/CdSe-SWNT hybrids - Hu, Liangbing (2011)
On account of their nano-scale size, large aspect ratio and high conductivity, single-walled carbon nanotubes(SWNTs) have emerged as an attractive choice for conducting composite materials. [1–10] Composites in corporating SWNTs show percolation dominated conductivity with a much lower volume threshold (volumefraction≈10–5), compared to those with nanoparticles.[11–13] Two-thirds of SWNTs a rep-typesemicon-ductors with holes as the charge carriers.Using the hole-blocking nature of SWNTs, conducting polymer shaving SWNTs as dopants are effectively used as the hole buffering [14] and electron transport[15] layers in organic light-emitted diodes(OLEDs). For the active layer of OLEDs and organic photovoltaic(OPV) devices, incorporation of SWNTs enhances the charge separation and facilitates charge transport, hence improving the performance, i.e., the short circuit current, the filling fact or and power conversion efficiency.[16–19] However, since SWNTs are a mixture of metallic and semi-conducting nano tubes with a small bandgap(≈0.6eV), both electrons and holes in the composite matrix prefer[14] to transfer on to and then be quenched on the SWNTs.